Capping Biological Quantum Dots with the Peptide Clpffd to Increase Stability and to Reduce Effects on Cell Viability - Vasquez-Guzman, C (Springer Netherlands, 2016)
Highly fluorescent nanoparticles, or quantum dots, have multiple applications in biology and biomedicine; however, in most cases, it is necessary to functionalize them to enhance their biocompatibility and selectivity. Generally, functionalization is performed after nanoparticle synthesis and involves the use of molecules or macromolecules having two important traits: specific biological activity and functional groups that facilitate nanoparticle capping (i.e. atom–atom interaction). For this reason, we carried out a simple protocol for the chemical synthesis of cadmium telluride quantum dots capped with glutathione, and we then functionalized these nanoparticles with the amphipathic peptide CLPFFD. This peptide attaches selectively to β-Amyloid fibres, which are involved in Alzheimer’s disease. Our results show that the optical properties of the quantum dots are not affected by functionalization with this peptide. Infrared spectra showed that cadmium telluride quantum dots were functionalized with the peptide CLPFFD. In addition, no significant differences were observed between the surface charge of the quantum dots with or without CLPFFD and the nanocrystal size calculated for HR-TEM was 4.2 nm. Finally, our results show that quantum dots with CLPFFD are stable and that they resulted in a significantly reduced cytotoxicity with respect to that induced by quantum dots not conjugated with the peptide. Moreover, the results show that the CLPFFD-functionalized nanoparticles bind to β-Amyloid fibres. © 2016, Springer Science+Business Media Dordrecht.